The Involvement of the nif-Associated Ferredoxin-Like Genes fdxA and fdxN of Herbaspirillum seropedicae in Nitrogen Fixation - Souza, Andre L.F., Universidade Federal do Parana, CP, Brazil; Invitti, Adriana L., Universidade Federal do Parana, CP, Brazil; Rego, Fabiane G.M., Universidade Federal do Parana, CP, Brazil; Monteiro, Rose A., Universidade Federal do Parana, CP, Brazil; Klassen, Giseli, Universidade Federal do Parana, CP, Brazil; Souza, Emanuel M., Universidade Federal do Parana, CP, Brazil; Chubatsu, Leda S., Universidade Federal do Parana, CP, Brazil; Pedrosa, Fabio O., Universidade Federal do Parana, CP, Brazil; Rigo, Liu U., Universidade Federal do Parana, CP, Brazil (The journal of microbiology, 2010)
The pathway of electron transport to nitrogenase in the endophytic β-Proteobacterium Herbaspirillum seropedicae has not been characterized. We have generated mutants in two nif-associated genes encoding putative ferredoxins, fdxA and fdxN. The fdxA gene is part of the operon nifHDKENXorf1orf2fdxAnifQmodABC and is transcribed from the nifH promoter, as revealed by lacZ gene fusion. The fdxN gene is probably co-transcribed with the nifB gene. Mutational analysis suggests that the FdxA protein is essential for maximum nitrogenase activity, since the nitrogenase activity of the fdxA mutant strain was reduced to about 30% of that of the wild-type strain. In addition, the fdxA mutation had no effect on the nitrogenase switch-off in response to ammonium. Nitrogenase activity of a mutant strain lacking the fdxN gene was completely abolished. This phenotype was reverted by complementation with fdxN expressed under lacZ promoter control. The results suggest that the products of both the fdxA and fdxN genes are probably involved in electron transfer during nitrogen fixation.